Initial presentation of granulomatosis with polyangiitis as urethral mass mimicking urethral cancer: A case report - Namita Mohanty; Thinn San; Stephen Bell; Rasmita Jalla; James Williams; Isaac Fordjour; Naomi Siddiquee; Larisa Gavrilova-Jordan; Laura Carbone; Rachel Elam (Elsevier, 2023)
Granulomatosis with polyangiitis (GPA) is a type of vasculitis in which granulomas deposit in small and medium-size vessels causing inflammation. It frequently affects the respiratory tract, both upper and lower tracts. Glomerulonephritis commonly occurs as well, and other systems can be affected such as the integumentary system and peripheral nervous system. Rarely, urogenital signs and symptoms are present. This report describes a case of a 19-year-old woman who presented with lower urinary tract symptoms and a urethral mass and was subsequently diagnosed with GPA. She responded well to treatment with corticosteroids, rituximab, and avacopan. This case highlights the importance of considering alternative diagnoses when a young woman presents with refractory urinary symptoms. It also highlights fertility issues relative to treatment of GPA that are of interest to the practicing obstetrician/gynecologist.